THE UNDERSTANDING OF PRIMARY SCHOOLS TEACHERS OF THE CONCEPT OF ESD: A MILESTONE TO MANIFEST SDGs - Kismiati, Dyah Aniza; Masbukhin, Faizal A.A (Universitas Bhinneka PGRI, 2025)
Education for Sustainable Development (ESD) is a milestone to achieve Sustainable Development Goals. The concept of Education for Sustainable Development must be instilled as early as possible so that students are accustomed to behaving and behaving with the importance of environmental sustainability. This survey research was conducted with the aim of finding out how deep the understanding of teachers. The study was conducted on 46 primary school teachers in Indonesia with random sampling. These respondents are teachers who teach in grades 1 to 6. The data collection instrument uses questionnaires with closed question types (yes or no responses) and open question types to explore the understanding of the concept of Education for Sustainable Development and its implementation in primary school. Research data is analyzed descriptively and presented in the form of percentages, tables and diagrams. The results of the analysis showed that most (52%) teachers did not understand the concept of ESD, while another 48% have understood ESD concepts, although only 68% of teachers who are understand with ESD concepts have integrated ESD concepts in learning.. This is due to several things including the lack of upgrading teacher knowledge who are less concerned about the problems that are currently occurring and the lack of government socialization related to the importance of ESD for the sustainability of life.The recommendation to the results of this study is that the government should pay special attention to conducting trainings for primary school teachers related to the concept of ESD and how to implement it in primary school